2004
DOI: 10.1038/sj.eye.6701346
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of bone marrow-derived stem and progenitor cells in the pathogenesis of pterygium

Abstract: Aims To evaluate the involvement of multipotential stem and progenitor cells in the pathogenesis of pterygium. Methods Paraffin-embedded and snap-frozen primary pterygium (n ¼ 10) were serially sectioned and analysed immunohistochemically to determine the expression level of AC133 (marker for the primitive haematopoietic progenitors), CD34 (marker for the haematopoietic progenitor cells and endothelium), c-Kit (marker for haematopoietic and stromal progenitor cells), and STRO-1 (a differentiation antigen prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 24 publications
3
11
1
Order By: Relevance
“…Our work revealed that bone marrow-derived CECs lost expression of stem cell markers upon exit from the bone marrow. Surprisingly, our studies also demonstrated that the expression of the often used stem cell marker CD117 is lost before CD133 [5][6][7][8][9][10][11]. This distinction implies that CD133 expression may represent a more reliable marker of CEP cells.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Our work revealed that bone marrow-derived CECs lost expression of stem cell markers upon exit from the bone marrow. Surprisingly, our studies also demonstrated that the expression of the often used stem cell marker CD117 is lost before CD133 [5][6][7][8][9][10][11]. This distinction implies that CD133 expression may represent a more reliable marker of CEP cells.…”
Section: Discussioncontrasting
confidence: 42%
“…Circulating endothelial progenitors are distinguished by the presence of at least 1 stem cell marker, typically CD117 0022-3468/$ -see front matter D 2007 Elsevier Inc. All (c-kit ligand receptor) or CD133 (prominin-1) [5][6][7][8][9][10][11]. Initially identified after sex-mismatched bone marrow transplant [12,13], CEPs have since been distinguished functionally both in vitro and in vivo.…”
mentioning
confidence: 99%
“…In the mouse embryonic and adult eyes, prominin-1/CD133 was shown to be expressed in the retina [39]. In the human eye, CD133 immunoreactivity was demonstrated in epithelial and single stromal cells of pterygium [40,41], in hemangioblastoma associated with Von Hippel-Lindau disease [42], and in choroidal neovascularization secondary to agerelated macular degeneration [43], suggesting an involvement of stem cells in these processes. CD133 was also detected in retinoblastoma cell lines [23].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous growth factors and inflammatory cytokines released by corneal epithelial cells, keratocytes, endothelial cells and recruited immune cells may act in cooperation to promote the corneal wound healing [169]. Moreover, in certain pathologies, the corneal remodeling may be accompanied by a neovascularization of corneal stroma, ulceration, chronic inflammation, opacification, and scarring associated with the invasion of the corneal surface by the conjunctival epithelial cells "conjunctivalization", and ultimately may lead to blindness and a partial or complete loss of vision [169,179]. The available treatments for severely injured ocular surface may consist to stimulate the residual limbal CESCs in patient's limbus in vivo by using appropriate growth factors or alternatively to perform an autologous or allogenic graft transplant of the new exogenous and functional limbal CESCs from patient's or host donor's limbus onto damaged ocular surface of diseased eye.…”
Section: Eye Diseases and Stem Cell-based Treatmentsmentioning
confidence: 99%